Покращення вивчення іноземних мов за допомогою моделей обробки природної мови - Тимахов, Д. В. (ХНУРЕ, 2023)
This article explores the various ways in which NLP models can help learners to improve their reading, writing, listening, and speaking skills in the English language. The article outlines how NLP models can generate topic based word lists for further study, check word usage in context, correct sentence errors, explain word meanings in context, and simplify complex texts. The benefits of using NLP models in language learning, including increased accuracy, efficiency, and accessibility, are also discussed. Additionally, potential future innovations in NLP models are highlighted. The article concludes by emphasizing the potential of NLP models to transform the language learning experience in the future